Resistance to multiple fungicides in Botrytis cinerea isolates from commercial strawberry fields in the eastern USA - De-Vicente-Moreno, Antonio; Fernández-Ortuño, Dolores; Grabke, A; Bryson, P.K.; Li, X.P.; Schnabel, G. (My University, 2014)
Chemical control of gray mold of strawberry caused by Botrytis cinerea Pers. is essential to prevent pre- and postharvest fruit decay; however, resistance to multiple chemical classes of fungicides including APs (cyprodinil), DCs (iprodione), MBCs (thiophanate-methyl), PPs (fludioxonil), QoIs (pyraclostrobin), SBIs (fenhexamid), or SDHIs (boscalid) is a well-known and well-described phenomenon in B. cinerea from strawberry fields in Florida, Germany, North Carolina, and South Carolina. As part of a resistance-monitoring program conducted during 2012 and 2013, a total of 1,890 B. cinerea isolates where collected from 10 states in the eastern USA. The isolates were analyzed for fungicide resistance using a mycelial growth assay. The overall resistance frequencies in 2012 for thiophanate-methyl, pyraclostrobin, boscalid, cyprodinil, fenhexamid, iprodione, and fludioxonil were 76, 42, 29, 27, 25, 3, and 1%, respectively. Frequencies in 2013 were 85, 59, 5, 17, 26, 2, and 1%, respectively. Isolates were resistant to either one (23%), two (18%), three (19%), four (14%), five (3%) or six (0.1%) chemical classes of fungicides in 2012. In 2013 this distribution was 24%, 29%, 26%, 8%, 2%, 0.3%, respectively, and also 0.3% (6 isolates) were resistant to all classes of fungicides. Resistance to thiophanate-methyl, iprodione, boscalid, pyraclostrobin and fenhexamid was based on target gene mutations in β-tubulin, bos1, sdhB, cytb, and erg27, respectively. Isolates were MDR1 or MDR1h dependent on sensitivity to fludioxonil and variations in transcription factor mrr1. Expression of ABC transporter atrB was highest in MDR1h isolates. The discovery of B. cinerea isolates resistant to all registered site-specific fungicides for gray mold control represents an unprecedented milestone of resistance development in B. cinerea that signals a failure of current anti-resistance management strategies.
Keywords: Microbiología